Ambulatory blood pressure monitoring in children: A retrospective single-center study - Ahlenius, Mark; Koek, Wouter; Yamaguchi, Ikuyo (Frontiers in Pediatrics, 2023)
Objectives: (1) Compare 24-hour ambulatory blood pressure monitoring (ABPM) diagnoses in a pediatric population with the new 2022 guidelines to the original diagnoses with the 2014 guidelines. (2) Determine whether findings of hypertension from ABPM could be predicted from prior patient data. (3) Determine whether ABPM readings could predict left ventricular mass index (LVMI) in patients who obtained an echocardiogram (ECHO). Study design: Single-center retrospective study on patients referred to Pediatric Nephrology Clinic for evaluation of elevated blood pressure who underwent ABPM from 2015 to 2018. Predictions of hypertension were obtained using a logistic regression model, and predictions of LVMI were performed using regression models including (a) the wake systolic and diastolic BP indices, or (b) additionally including the standard deviation (SD) of wake SBP and DBP. Results: With the change in 2022 to new ABPM guidelines from the AHA, comparing the old and new guidelines led to 70% of previous pre-hypertensive diagnoses now meeting criteria for diagnosis of hypertension, and a rise from 21% of the ABPMs meeting criteria for hypertension to 51% now meeting criteria. In a logistic regression model, prior patient data was not predictive of a diagnosis of hypertension from ABPM (Nagelkerke’s R2 = 0.04). Among the individual variables studied, none were statistically significant. For prediction of LVMI, the model including the SD of wake SBP and DBP was superior to the model that did not include these variables (p= 0.044; adjusted R2 = 0.11 versus -0.02). Conclusions: In our patient population, the new ABPM guidelines led to a significant increase in diagnoses of hypertension. Prior patient data was not sufficient to predict a diagnosis of hypertension from ABPM, supporting the need for evaluation by ABPM as the gold standard. Our analysis of the relationship between ABPM readings and LVMI supports the hypothesis that systolic BP variability contributes to increased LVMI. These data are consistent with growing evidence in the adult literature that BP variability detected by ABPM is associated with left-ventricular hypertrophy